Los préstamos ortogados y la morosidad de la banca múltiple en el periodo post pandemia 2020 - 2021 - Soria Rios, Jair Ruperto (2022)
Credit is required for business growth, especially in the post-pandemic period. The objective of the present investigation is to determine the relationship between the loans granted and the delinquency of the Banca Múltiple de Loreto in the post-pandemic period 2020 - 2021. Based on this objective, the present Quantitative type study is carried out, level Correlational and non-experimental design. The investigation concludes that there is an inverse relationship between the balance of the loans granted and the delinquency of the Banca Múltiple de Loreto, in the post-pandemic period 2020 - 2021, validated by the Correlation Coefficient r = -0.871899756; which shows a very good inverse statistical association between the independent variable (balance of loans granted) and the dependent variable (default). Loans granted by Multiple Banking did not grow strongly in the post-pandemic period, but rather showed a linear behavior, having registered the maximum value in November 2020 with S/. 2,107.00 million; and the minimum in January 2021 with S/. 1,541.00 million. In the same way, the delinquency of Multiple Banking remained in the same range, without abruptly triggering due to the pandemic, being the lowest in August 2020 with 6.30%, and the highest in December 2021 with 9.30%. The delinquency of Multiple Banking was greater than that of the Financial System during the post-pandemic period.